USSR and revival of Indonesian Communist Party - L. M. Efimova (Vestnik MGIMO-Universiteta)
For more than two generations, historians have been asking themselves whether Moscow participated in the organizational and ideological revival of the Indonesian Communist Party (PKI) in 1951-53. Some authors believe that the Indonesian communists defined the new party strategy and tactics independently from either Moscow or Beijing. Scholars have been eager to know whether Moscow participated directly in the promulgation of the new PKI line. Newly released documents show that Stalin played an active and personal role in the process of discussing and refining a new program for the PKI. The main ideas Stalin expressed during his discussions with the Indonesian Communists were incorporated into the new PKI program adopted in 1954, as well as in articles and speeches of PKI General Secretary Dipa Nusantara Aidit.